+0  
 
0
269
1
avatar
ln 7 + ln (n - 2) = ln 6n
Guest Apr 13, 2012
 #1
avatar+3079 
0
ln( 7 ) + ln (n - 2) = ln( 6n)
with: ln( x*y ) = ln(x)+ln(y)

ln ( 7 * (n-2) ) = ln( 6n )
e^x on both sides (if n>0)

7 * (n-2) = 6n
7n - 14 = 6n
7n - 6n = 14
n = 14
admin  Apr 13, 2012

17 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.